2020
DOI: 10.1080/22221751.2020.1799723
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in Akt/mTOR/HIF-1 signaling identified by proteo-transcriptomics of SARS-CoV-2 infected cells

Abstract: How severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections engage cellular host pathways and innate immunity in infected cells remains largely elusive. We performed an integrative proteo-transcriptomics analysis in SARS-CoV-2 infected Huh7 cells to map the cellular response to the invading virus over time. We identified four pathways, ErbB, HIF-1, mTOR and TNF signaling, among others that were markedly modulated during the course of the SARS-CoV-2 infection in vitro. Western blot validation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
266
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(308 citation statements)
references
References 46 publications
19
266
0
2
Order By: Relevance
“…Recently, Appelberg et al conducted an integrative proteo-transcriptomics analysis of Huh7 cells responding to SARS-CoV-2 infection, and identified ErbB, HIF-1, mTOR, and TNF signaling pathways that were significantly regulated during SARS-CoV-2 infection in vitro. 78 They further demonstrated that the Akt inhibitor MK-2206, targeting the mTOR signaling pathway, was able to significantly reduce the replication of SARS-CoV-2. Moreover, another recent study investigated the translatome and proteome of Caco-2 cells in response to SARS-CoV-2 infection in vitro, and discovered that several cellular pathways linked to translation, proteostasis, splicing, carbon metabolism, and nucleotide metabolism were reshaped during viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Appelberg et al conducted an integrative proteo-transcriptomics analysis of Huh7 cells responding to SARS-CoV-2 infection, and identified ErbB, HIF-1, mTOR, and TNF signaling pathways that were significantly regulated during SARS-CoV-2 infection in vitro. 78 They further demonstrated that the Akt inhibitor MK-2206, targeting the mTOR signaling pathway, was able to significantly reduce the replication of SARS-CoV-2. Moreover, another recent study investigated the translatome and proteome of Caco-2 cells in response to SARS-CoV-2 infection in vitro, and discovered that several cellular pathways linked to translation, proteostasis, splicing, carbon metabolism, and nucleotide metabolism were reshaped during viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were hereby quantified with TMT labeling and reversed-phase liquid chromatography tandem mass spectrometry (RPLC-MS/MS). 62 In another proteomics study with SARS-CoV-2, which also utilized TMT-based quantification, Caco-2 cells (human colorectal tumor cell line) were infected and studied over time. Cellular pathways, such as cholesterol metabolism, translation, splicing, and carbon metabolism, were identified to be reshaped during viral infection.…”
Section: Coronavirusesmentioning
confidence: 99%
“…Virus production was significantly reduced by the inhibition of the mTOR signaling pathway using Akt inhibitor MK-2206. Further, the authors suggested profound studies are required for the treatment of COVID-19 patients (Appelberg et al 2020 ).…”
Section: Proteomics For Sarsmentioning
confidence: 99%